Morphological and Anatomical Characters of Lowland-Black Rice Grains in the Northeast of Thailand - ธรรมวงศา ธีระ; สนิทชน จิรวัฒน์; มีสวาสดิ์ อมรรัตน์; อิฐรัตน์ ปิยะรัตน์ (KKU Science Journal, 2012)
Twenty six specimens of lowland-black rice were collected from cultivation areas in the northeast of Thailand between 2008 and 2009. Morphology and anatomy of their grains were investigated. The results showed that the color of grain, the shape of grain, the shape, the color and the length of brown rice, the surface of lemma, and the thickness of brown rice coat are taxonomic value.